Population genetic and phenotypic analyses of Aspergillus fumigatus strains from global soil samples - Korfanty, Gregory (My University, 2023)
Fungal populations occupy a vast number of ecological niches across many geographic areas around the planet. Fungi act as essential nutrient recyclers, playing key roles as saprophytes, mutualists, and pathogens. As humans, we use these broad properties of fungi in biochemical and pharmaceutical industries, creating a plethora of products ranging from antimicrobials to food products. However, certain fungal species have become a devastating burden on human public health. Of these fungal species, my PhD thesis has focused on the critically important mold Aspergillus fumigatus. This mold is an opportunistic human pathogen, being the leading etiological cause of the spectrum of diseases termed aspergillosis that yearly affects over 8,000,000 people worldwide. In addition, the rising number of antifungal resistant strains around the world, especially within environmental populations, is of critical concern. Given that almost all aspergillosis infections result from environmental strains, and that soil is a major ecological niche for A. fumigatus, my thesis focused on characterizing genetic and phenotypic aspects of soil isolates of A. fumigatus obtained from many geographic and climatic regions around the world. My analyses revealed extensive allelic and genotypic diversity within and among populations. These A. fumigatus populations were defined by both historical differentiations, high gene flow, non-random recombination, and high susceptibility to triazole antifungals. Additionally, I tested the sexual fecundity of a subset of these global strains and found that geographic and genetic distance between the pairs of parental strains had little effect on sexual fecundity. Lastly, my research found broad variations in growth of a global sample of A. fumigatus strains at different temperatures. Again, no relationship of either geographic or genetic distance on strain growth was observed. Overall, my research highlights the extraordinary nature of A. fumigatus populations to quickly spread and adapt across diverse and complex environments.
A thesis submitted to the school of graduate studies in the partial fulfillment of the requirements for the degree doctor of philosophy.
Keywords: Aspergillus fumigatus; Population structure; Global soil; Thermal adaptibility; Sexual fitness; Fungal isolation; Genetic diversity; Triazole resistance; Arctic; Phenotypic variation